Environmental risk factors for canine toxoplasmosis in a deprived district of Botucatu, SP, Brazil - Camossi, L. G. [UNESP]; Faccioli, P. Y. [UNESP]; Menozzi, B. D. [UNESP]; Daher, S. R. [UNESP]; Langoni, H. [UNESP] (FapUNIFESP (SciELO), 2008)
Toxoplasmosis is a worldwide zoonosis caused by Toxoplasma gondii that can infect a large variety of animals, including humans. The present study aimed to evaluate the frequency of auti-T.gondii antibodies in dogs from a peripheral district of Botucatu and to establish the association among some epidemiological variables in order to evaluate risk factors for toxoplasmosis infection. Serum samples from dogs were screened using an indirect fluorescent antibody (IFA) test. Anti-T.gondii antibody prevalence was 56%. The highest titer was 1024 (1.79%) and the most frequent titers were 16 (57.14%) and 64 (33.93%). The chi-square (X2) test revealed significant association among variables such as dog access to street, ingestion of raw meat and presence of synantropic animals in the domestic environment. These results demonstrate that toxoplasmosis is present in dogs from Jardim Santa Elisa district.
Keywords: Dogs; IFA; Risk factors; Toxoplasma gondii